Analisis Bibliometrik Industri Kreatif Berkelanjutan di Indonesia - Supinardi, Bambang; Purwantoro, Nugroho (EKONOMI DAN BISNIS DIGITAL, 2024)
This paper aims at providing an overview and synthesis of the existing body of knowledge about Creative Industry in Indonesia. Special attention is paid to the articles directly linked with sustainability creative industries in Indonesia. Design/methodology/approach – A bibliometric analysis was performed over 925 documents extracted from the Google Scholar database, using PoP, Zotero, and VOS viewer software programs. Findings – Publications related to the sustainable creative industry are still very minimal. The publication mainly reviews case studies and analyzes of the phenomena of creative industry activities in a narrow, local and thematic way. There have not been many publications regarding the theory, direction and future of sustainable industries globally. Social implications – The development of scientific knowledge about sustainability of creative industry puts this social claim on the spotlight of business management studies, helping bussinesmen and to reduce the environmental impact of corporate activities. Studying sustainability will help to reduce its frequency and, therefore, heal the planet. Conclusion - Facing the increasingly threat of damage due to developments in human needs, the sustainable industrial sector absolutely needs attention. Likewise in the creative industry sector. More attention is needed from the government and creative industry players to place greater emphasis on environmentally friendly and socially friendly industries. Thus, Scientific studies that examine sustainable creative industries must be increased and become a concern for all of us